Answer:
![y=2x-9](https://tex.z-dn.net/?f=y%3D2x-9)
Step-by-step explanation:
you have the line
![-3x-6y=17](https://tex.z-dn.net/?f=-3x-6y%3D17)
clearing for y:
![-6y=17+3x\\y=\frac{17}{-6} +\frac{3}{-6} x\\y=-\frac{1}{2} x-\frac{17}{6}](https://tex.z-dn.net/?f=-6y%3D17%2B3x%5C%5Cy%3D%5Cfrac%7B17%7D%7B-6%7D%20%2B%5Cfrac%7B3%7D%7B-6%7D%20x%5C%5Cy%3D-%5Cfrac%7B1%7D%7B2%7D%20x-%5Cfrac%7B17%7D%7B6%7D)
we have an equation of the form
![y=mx+b](https://tex.z-dn.net/?f=y%3Dmx%2Bb)
the number that accompanies the x is the slope, and the number alone is the intercept with the y-axis
the slope m is:
![m=-\frac{1}{2}](https://tex.z-dn.net/?f=m%3D-%5Cfrac%7B1%7D%7B2%7D)
i will call the slope of the new line ![m_{2}](https://tex.z-dn.net/?f=m_%7B2%7D)
so for two perpendiculares lines we must have:![m*m_{2}=-1](https://tex.z-dn.net/?f=m%2Am_%7B2%7D%3D-1)
and from this we can find the new slope:
![m_{2}=\frac{-1}{m} \\\\m_{2}=\frac{-1}{\frac{-1}{2} } \\m_{2}=2](https://tex.z-dn.net/?f=m_%7B2%7D%3D%5Cfrac%7B-1%7D%7Bm%7D%20%5C%5C%5C%5Cm_%7B2%7D%3D%5Cfrac%7B-1%7D%7B%5Cfrac%7B-1%7D%7B2%7D%20%7D%20%5C%5Cm_%7B2%7D%3D2)
the new slope is 2,
so far we have that the new line is:
![y=2x+b](https://tex.z-dn.net/?f=y%3D2x%2Bb)
so now we have to find the intercept with the y axis (
) of the new line, since it passes trough (6,3) ---> x = 6 when y = 3
substituting these x and y values in
:
![3=2(6)+b\\3=12+b\\b=3-12\\b=-9](https://tex.z-dn.net/?f=3%3D2%286%29%2Bb%5C%5C3%3D12%2Bb%5C%5Cb%3D3-12%5C%5Cb%3D-9)
and finally, the equation of the new line that is perpendicular to the original line is:
![y=2x-9](https://tex.z-dn.net/?f=y%3D2x-9)